The Climate Crisis Will Not Wait - Matilda Gettins (Intereconomics, 2020)
Climate communication is an essential step towards changing the rules. Policies with a large-scale impact on the economy and individuals, such as a high carbon tax, must be justified in terms of their proportionality.
Keywords: 330; Klimawandel; Klimapolitik